Representasi Makna Kematian pada Individu dalam Perspektif Keislaman - Brian Rinalda Prawikasena; Aning Sofyan (Bandung Conference Series: Communication Management, 2022)
Abstract. Film is one of the means of entertainment in which there is a story or event from a true or fictional story. Film is also a means of education, information as well as distribution of works of art. Along with the development of the times, many films were produced with horrific themes such as violence, death and other terrible things. Therefore, the researcher chose the film "Lords Of Chaos" because in the film it tells a story that will be easily considered as absurd if it is not based on actual events and the researcher wants to analyze the aspects of death from an Islamic perspective. What makes researchers interested is that the lives of individual members of the Mayhem band are inversely proportional to the Islamic point of view and the researcher wants to examine more deeply about the Representation of Death in an Islamic Perspective. The purpose of this study was to determine the meaning of denotation, connotation and myths that contain elements of Representation of Death in the Lords of Chaos film. This research method uses a qualitative research method with the semiotic approach of Roland Barthes. Data collection techniques in this study are documentation and literature study. This study obtained the results that there are denotative, connotative and mythical meanings contained in this film and there are also symbols that represent death. The meaning of denotation in this film is in several scenes that show actions that are prohibited by Islam. The connotative meaning in the scene that the researcher chose is an attitude or action that doesn't make sense and is not afraid of death which is a positive attitude for Islam if it is balanced with self-introspection and also has a good attitude towards Allah SWT. Staying on His way is the right thing to do. Introspection of the sins that have been committed and improve yourself by getting closer to Allah SWT. Abstrak. Film merupakan salah satu sarana hiburan di mana di dalamnya terdapat sebuah cerita maupun peristiwa kisah nyata ataupun fiksi. Film juga menjadi sarana edukasi, informasi juga penyaluran karya seni. Seiring perkembangan zaman film banyak diproduksi dengan mengangkat tema-tema yang mengerikan seperti kekerasan, kematian dan hal mengerikan lainnya. Maka dari itu peneliti memilih film “Lords Of Chaos” karena dalam film tersebut menceritakan salah satu kisah yang akan dengan mudah dianggap sebagai tidak masuk akal jika tidak didasarkan pada peristiwa aktual dan peneliti ingin menganalisis mengenai aspek kematian dalam perspektif keislaman. Hal yang membuat peneliti tertarik adalah kehidupan yang dijalani oleh individu anggota grup band Mayhem sangat lah berbanding terbalik dengan sudut pandang Islam dan peneliti ingin mengkaji lebih dalam perihal Representasi Kematian dalam Perspektif Keislaman. Tujuan penelitian ini adalah untuk mengetahui makna denotasi, konotasi dan mitos yang mengandung unsur Representasi Kematian dalam film Lords of Chaos. Metode penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan semiotika Roland Barthes. Teknik pengumpulan data pada penelitian ini adalah dokomentasi dan studi kepustakaan. Penelitian ini memperoleh hasil yaitu adanya makna denotasi, konotasi dan mitos yang terdapat dalam film ini dan juga terdapat simbol-simbol yang merepresentasikan kematian. Makna denotasi pada film ini yaitu dalam beberapa adegan yang menunjukan tindakan yang dilarang oleh Islam. Makna konotasi pada adegan yang peneliti pilih yaitu sikap maupun tindakan yang tidak masuk akal untuk dilakukan dan tidak takut akan kematian yang merupakan sebuah sikap positif bagi Islam jika diimbangi dengan intopeksi diri dan juga berprasangka baik kepada Allah SWT. Tetap pada jalan-Nya merupakan tindakan yang benar. Intropeksi akan dosa-dosa yang sudah diperbuat dan memperbaiki diri dengan mendekatkan diri kepada Allah SWT.